Action research, feminist pedagogy and blended learning: Towards a holistic and practical approach - Lai, Suat Yan; Singaravelloo, Kuppusamy; Sanusi, Junedah (2017)
The research focuses on the adoption of action research to address the lack of participatory learning in a student centered classroom. It embodies a holistic process that takes into consideration the pedagogical context that is feministic in nature for the course Gender Issues in the Media. The focus is not solely on technique or the use of technology but encompasses an understanding of the perspective of the learners of elements in a course that enables their learning level to be of the highest quality. Innovatively, it also seeks to explore the use of mobile telephone to enable participatory learning on the go. However, based on feedback from learners, there are two hindrances to this. Firstly, the interface of the mobile phone is not user friendly enough for such purposes. Secondly, there is difficulty in concentrating on the discussion and give a thoughtful feedback due to the various distractions, particularly, notification of incoming messages be it from their whatsapp application, email messages or the like. The adoption of action research signifies that the instructor herself is also a learner who seeks to understand the learning process of the learners of the course. Following from feedback from students and the observer in the classroom, small group discussions was adopted throughout the remainder of the course. It is found that there is a need to be more process oriented and scale down on the content as group discussion, while enables participatory learning, is much more time consuming. Notably, learners expressed that they like the element of learning gender issues from watching movies that was already part and parcel of the course rather than from theories. It seems that it is a more practical and fun way to learn and engages with them affectively as well. Incorporating the feminist pedagogy that takes into account real life experiences including personal experiences a field trip was also organized to a production house to explore gender issues in the media. In addition, group discussion was held to analyze the ways in which the coverage of athletes during the recent Olympics were gendered.